Dukungan Spiritual Pastoral Konseling terhadap Keberlanjutan Pemberdayaan Ekonomi Masyarakat Miskin - Sri Firgita Ayu; Chaterine Cristianne Linggi; Raema Rosdiana Lisu; Sindi Paliling (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Poverty remains a multidimensional crisis requiring holistic interventions that integrate spiritual and economic dimensions. This study aims to analyze forms of spiritual support in pastoral counseling for the poor and identify mechanisms through which such support contributes to the sustainability of economic empowerment programs. Using a qualitative approach with systematic literature review, data were collected from academic journals, theological texts, and previous research published between 2006-2025, analyzed through thematic content analysis. The findings reveal five integrated forms of spiritual support: spiritual-theological support for restoring meaning and hope, transformative psychosocial accompaniment integrating counseling techniques with faith values, communal empowerment based on Christian values creating sustainable support ecosystems, practical life skills guidance and economic capacity development, and advocacy facilitating access to structural resources. These forms contribute to sustainability through five mechanisms: mindset transformation from helplessness to self-agency, strengthening resilience and adaptive capacity, forming social networks and social capital, integrating Christian values in work ethics, and establishing continuous mentoring systems with participatory evaluation. This study confirms that spiritual support is an essential element determining the long-term success of economic empowerment programs for the poor.